Analisis Pengaruh Hambatan Samping Terhadap Kinerja Ruas Jalan Veteran Selatan - Indrian Citra; Rais Rachman; Monika D.M Palinggi (Paulus Civil Engineering Journal, 2020)
Side barriers are activities next to the road that disrupt the smooth flow of traffic. The path should be used for the unseized traffic flow for the vehicle to stop. As well as many outbound access to the vehicles from the land all the way increases the density of the road. The required road segments should correspond to the existing segments without being interrupted by side barriers. In fact, this road is solid enough at a certain time with a car park and public transportation that lowers passengers along the way. In addition, the number of pedestrians is running or crossing the road segments, and the number of motorised vehicles coming out of the side of the road and slow-moving currents. The research aims to provide a side barrier to whether the traffic is the cause of congestion on South veterans ' roads, or the current dating to the major Independence Pioneer Road section. From the results of data analysis obtained average peak traffic flow during 3 days observation of 1,606.6 SMP/hr, side barriers at the peak current of 283.7 pcu/15 minutes of road capacity of 1474.4 pcu/hr, average degree of saturation of 1.08.